2002
DOI: 10.1038/sj.ejhg.5200884
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a locus on chromosome 2q11 at which recessive amelogenesis imperfecta and cone-rod dystrophy cosegregate

Abstract: A consanguineous Arab pedigree in which recessive amelogenesis imperfecta (AI) and cone-rod dystrophy cosegregate, was screened for linkage to known retinal dystrophy and tooth abnormality loci by genotyping neighbouring microsatellite markers. This analysis resulted in linkage with a maximum lod score of 7.03 to the marker D2S2187 at the achromatopsia locus on chromosome 2q11, and haplotype analysis placed the gene(s) involved in a 2 cM/5 Mb interval between markers D2S2209 and D2S373. The CNGA3 gene, known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Two kindreds have been reported with 2q11 linked predisposition to recessive progressive cone-rod dystrophy and amelogenesis imperfecta (Downey et al 2002;Michaelides et al 2004). Furthermore, mutations of the MERTK gene have so far only been associated with arRP (Gal et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two kindreds have been reported with 2q11 linked predisposition to recessive progressive cone-rod dystrophy and amelogenesis imperfecta (Downey et al 2002;Michaelides et al 2004). Furthermore, mutations of the MERTK gene have so far only been associated with arRP (Gal et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…2) all over the test field in both the eyes. Nobody in this family presented defects of tooth enamel found in amelogenesis imperfecta associated with progressive cone-rod dystrophy (Downey et al 2002;Michaelides et al 2004). …”
Section: Clinical Characteristics Of the Adrp Familymentioning
confidence: 93%
“…An autosomal-dominant, local hypoplastic form of AI (AIH2) has been mapped to a 4 Mb region of human chromosome 4q11-q21 that encompasses the gene encoding the ameloblast-specific protein ameloblastin, AMBN (MacDougall et al, 1997). Identification of a locus on chromosome 2q11 at which recessive AI and cone-rod dystrophy co-segregate has been reported (Downey et al, 2002). While AI is not in itself a fatal disease, the rapid attrition of teeth and consequent lack of ability to deal with even a soft diet that is characteristic of the condition must have been a serious handicap to survival in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage studies have reported the association of syndromic ARAI with a locus on chromosome 2 in one family (Downey et al 2002), but results in another four families that segregate with nonsyndrome ARAIs do not show linkage with this region (Michaelides et al 2004). To date, only four genes have been demonstrated to possess causal roles in the etiology of this type of AI: the ENAM gene, the genes that code for the enamel proteases MMP-20 and KLK4, and the gene encoding WDR72 (El-Sayed et al 2009).…”
Section: Phenotype-genotype Correlations In Autosomally Inherited Casesmentioning
confidence: 99%